An Empirical Study on Comparison in Fund Performance between Open-end Funds and Closed-end Funds in China - Huang, ya (2009)
In recent years open-end funds have replaced closed-end funds as the dominant products in China fund market in terms of both aggregate assets and growth rates. In this case it is widely concerned whether open-end funds really outperform closed-end funds. Thus this dissertation selects 26 open-end funds and 13 closed-end funds from 10 fund management companies and then compares their performance from Sep 2004 to Aug 2009 with average rate of return, Sharp ratio, Treynor measure, Jensen’s alpha, T-M model as methodologies. According to the empirical test, it is concluded that as for sharp ratio and selectivity, open-end funds are significantly superior to closed-end funds; but regarding other measures, no obvious difference is detected. Lastly, based on the study results some suggestions for investors, fund managers and related authorities are raised.